2018
DOI: 10.1007/s00792-018-1057-0
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR RNA-guided DNA cleavage by reconstituted Type I-A immune effector complexes

Abstract: Diverse CRISPR-Cas immune systems protect archaea and bacteria from viruses and other mobile genetic elements. All CRISPR-Cas systems ultimately function by sequence-specific destruction of invading complementary nucleic acids. However, each CRISPR system uses compositionally distinct crRNP [CRISPR (cr) RNA/Cas protein] immune effector complexes to recognize and destroy invasive nucleic acids by unique molecular mechanisms. Previously, we found that Type I-A (Csa) effector crRNPs from Pyrococcus furiosus funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…Recently, it was also demonstrated that like some other CARF-domain nucleases (see above), also Csx1 of P. furiosus was endowed with ring nuclease activity, self-inactivating its cOA activators [147]. Apart from additional biochemical studies focusing on the two other type I effector complexes in P. furiosus [80,81], in vivo immunity against engineered plasmid invaders was shown for all effector complexes independently by analyzing a plethora of cas (and accessory genes) mutants [122,147,179]. Recently P. furious has also become a model to study spacer acquisition, revealing that new extrachromosomal spacers are preferentially acquired from broken DNA ends, supplied by plasmids with rolling-circle rather than theta replication [33].…”
Section: Pyrococcus-shaping Crispr Crystalsmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, it was also demonstrated that like some other CARF-domain nucleases (see above), also Csx1 of P. furiosus was endowed with ring nuclease activity, self-inactivating its cOA activators [147]. Apart from additional biochemical studies focusing on the two other type I effector complexes in P. furiosus [80,81], in vivo immunity against engineered plasmid invaders was shown for all effector complexes independently by analyzing a plethora of cas (and accessory genes) mutants [122,147,179]. Recently P. furious has also become a model to study spacer acquisition, revealing that new extrachromosomal spacers are preferentially acquired from broken DNA ends, supplied by plasmids with rolling-circle rather than theta replication [33].…”
Section: Pyrococcus-shaping Crispr Crystalsmentioning
confidence: 96%
“…CRISPR type I systems in general employ a multi-subunit effector complex termed CRISPR-associated complex for antiviral defense (Cascade) which, upon PAM recognition and crRNA hybridization catalyzes protospacer degradation by the action of the Cas3 enzyme endowed with ssDNA-endonuclease (provided by an HD domain) and helicase activity. Cas3 nicks the strand opposite to the crRNA-protospacer heteroduplex and is then activated to processively cleave the upstream region [73][74][75][76][77][78][79][80][81] (c.f. Figure 1).…”
Section: Crispr Dna Interferencementioning
confidence: 99%
“…CrRNAs constitute prokaryotic immune system by assisting Cas proteins recognize and cut exogenous DNA. On phage infection, proteo-spacers are lysed by bacteria Cas protein complexes and integrated into the 5′ end of the CRISPR sites in host genome which are then transcribed into crRNAs and function as the template against phage proto-spacers once infected again [62][63][64].…”
Section: Perspectivesmentioning
confidence: 99%
“…Cas3 and Cas10 are considered as the signature genes for types I and III, respectively (Shmakov et al, 2017). Type III (B) Cmr is probably rare since it has been found to cleave targeted RNAs (Majumdar and Terns, 2019).…”
Section: Classification Of the Crispr/cas Systemmentioning
confidence: 99%